Spatial Manipulation via Four-Wave Mixing in Five-Level Cold Atoms - Gan, Shoufei (Frontiers in Physics, 2022)
We propose a scheme for the spatial manipulation via four-wave mixing (FWM) in a five-level atomic system. It is found that the FWM field can be easily manipulated by adjusting the corresponding parameters. Moreover, we show the superposition modes created by the interference between the FWM field and a same-frequency Gaussian beam, which can also be controlled via the corresponding parameters. Our research is helpful to understand and manipulate optical vortices and can be widely used in quantum computation and communication.